EDUCATIONAL EQUITY IN FINLAND: THE INFLUENCE OF PRIVATE SCHOOLS ON STUDENT ACHIEVEMENT BASED ON PISA RESULTS - Emil Gasimov; Xanim Mammadli (International Journal of Innovative Technologies in Social Science, 2025)
This study investigates the impact of private schools on students’ academic performance in Finland and conducts an empirical analysis using the results of the Programme for International Student Assessment in mathematics (PISA). Statistical modeling was performed using the ordinary least squares (OLS) method for data covering the period 2006-2022. The results of the study reveal that private schools have a statistically significant negative impact on PISA results. The coefficient of the PRIVATE variable is -0.000434, p-value 0.0264, proving that this effect is significant. The explanatory power of the model (R² = 0.747) indicates that public schools in Finland perform better in terms of academic performance. Finland’s education policy based on the principles of equality and inclusion is considered to be one of the main factors of this success.This study demonstrates the successful results of Finland’s publicly funded education system and emphasizes that it can be an exemplary model for countries seeking to create equal opportunities in education. A broader analysis of socio-economic factors, teacher quality, and international comparisons is recommended for future research.